Respostas

2014-07-07T11:15:40-03:00
a)ײ/12-×/2+2/3=0    (tirando o mmc de 12,2,3 )

x
²-6x+8=0
      12
x²-6x+8=0
Δ = b² - 4.a.c 
Δ = (-6)² - 4 . 1 . 8 
Δ = 36 - 4. 1 . 8 
Δ = 4


x = (-b +- √Δ)/2a
x' = (--6 + √4)/2.1       x'' = (--6 - √4)/2.1
x' = 8 / 2                    x'' = 4 / 2
x' = 4                         x'' = 2


b)×+1/2-ײ-1/3=0  
-x²+x +1/6=0             (tirando o mmc de 1,6 )
-6x²+6x+1=0
         6

-6x²+6x+1=0

Δ = b² - 4.a.c 
Δ = 6² - 4 . -6 . 1 
Δ = 36 - 4. -6 . 1 
Δ = 60

x = (-b +- √Δ)/2a
x' = (-6 + √60)/2.-6       x'' = (-6 - √60)/2.-6
x' = (-6 + 2√15)/-12       x'' = (-6 - 2√15)/-12
x' = (-3 + √15)/-6       x'' = (-3 - √15)/-6
x' = 1/3 - √15/6       x'' = 1/3 + √15/6

ou em decimais:

x' = -0,145   x'' = 1,145